Building gender considerations into livestock breeding in low- and middle-income countries - Galiè, Alessandra; Ojango, Julie M.K.; Farnworth, C.R.; Jumba, Humphrey; Roeven, L.; Marshall, Karen (Frontiers Media, 2025)
Livestock breeding programs are important in low- and middle-income countries because of the large number of livestock systems that can benefit from improved genetics. Local gender norms and dynamics shape livestock management in households and communities. They influence the ways in which women and men provide inputs, such as labor, finance, time, and knowledge into their livestock systems. They shape the specific needs, preferences, and distribution of the benefits derived from improved genetics. Breeding strategies must consider such gender dynamics to effectively contribute to various livestock systems and ensure that their benefits are equally shared within households and communities. However, the scoping review and key informant interviews conducted in this study revealed a sparse body of knowledge on gender-responsive livestock breeding. The purpose of this study is to develop a framework that can inform gender-responsive livestock breeding programs and, in so doing, develop a comprehensive knowledge base. The framework builds on the following key steps of a breeding program: (i) targeting, (ii) operationalization of the genetic improvement strategy, (iii) marketing and dissemination of genetic material, and (iv) ensuring equitable benefits from improved genetics. In each step, key gender questions are set out to help breeders and gender scientists think through and assemble the gendered information they need. These questions are of two types: gender-accommodative (to respond to gendered needs and priorities while reflecting existing gender norms and dynamics) and gender-transformative (to respond to gendered needs and priorities while allowing women to work towards their aspirations in livestock systems by challenging the discrimination of gender norms). The primary target readership is livestock breeders and social researchers working in low- and middle-income countries to improve livelihoods through livestock, with a focus on genetic improvement.